2017
DOI: 10.1016/j.mex.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Formation of supported lipid bilayers of charged E. coli lipids on modified gold by vesicle fusion

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…The result is consistent with previous studies, which showed at least ∼2 mM of Ca 2+ is necessary for the formation of PLE-SLB on SiO 2 /Si, mica, TiO 2 , indium tin oxide and gold (Dodd et al, 2008;Merz et al, 2008;Lopes et al, 2010;Unsay et al, 2013;Lind et al, 2015;Hsia et al, 2016;Konarzewska et al, 2017;Márquez and Vélez, 2017). In the previous studies of the bacterial mimic lipid bilayer, however, averaged response from the sample was mainly obtained using QCM and fluorescence microscopy (Dodd et al, 2008;Merz et al, 2008;Lopes et al, 2010;Unsay et al, 2013;Lind et al, 2015;Phan and Shin, 2015;Hsia et al, 2016;Konarzewska et al, 2017;Márquez and Vélez, 2017). The results in this study showed the heterogeneity of SLB especially at the threshold [Ca 2+ ] around 2.5 mM.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The result is consistent with previous studies, which showed at least ∼2 mM of Ca 2+ is necessary for the formation of PLE-SLB on SiO 2 /Si, mica, TiO 2 , indium tin oxide and gold (Dodd et al, 2008;Merz et al, 2008;Lopes et al, 2010;Unsay et al, 2013;Lind et al, 2015;Hsia et al, 2016;Konarzewska et al, 2017;Márquez and Vélez, 2017). In the previous studies of the bacterial mimic lipid bilayer, however, averaged response from the sample was mainly obtained using QCM and fluorescence microscopy (Dodd et al, 2008;Merz et al, 2008;Lopes et al, 2010;Unsay et al, 2013;Lind et al, 2015;Phan and Shin, 2015;Hsia et al, 2016;Konarzewska et al, 2017;Márquez and Vélez, 2017). The results in this study showed the heterogeneity of SLB especially at the threshold [Ca 2+ ] around 2.5 mM.…”
Section: Resultssupporting
confidence: 93%
“…As a bacterial model cell system, reconstituted Escherichia coli (E. coli) cell membrane has been studied (Dodd et al, 2008;Merz et al, 2008;Lopes et al, 2010;Unsay et al, 2013;Lind et al, 2015;Phan and Shin, 2015;Hsia et al, 2016;Konarzewska et al, 2017;Márquez and Vélez, 2017). Understanding the bacterial membrane system helps in revealing the mechanism of molecular recognition and material transportation during bacterial infection for medical technology.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations